Prefiks dalam Bahasa Sangkub - Hassan, Indra; Djou, Dakia N.; Masie, Sitti Rachmi (Jurnal Bahasa, Sastra, dan Budaya, 2024)
The problems addressed in this study are: 1) What types of prefixes are found in the Sangkub language? 2) What are the functions and meanings of prefixes in the Sangkub language? Therefore, this study aims to describe the types, functions, and meanings of prefixes in the Sangkub language. This study was conducted in North Bolaang Mongondow Regency, Sangkub District. The method used was a qualitative descriptive method. The data consisted of types of prefixes, their functions, and meanings in the Sangkub language. Data sources were obtained through interviews with residents of Sangkub District. Data collection methods included observation, interviews, note-taking, and recording. The results showed that six prefixes were identified in the Sangkub language. The functions of these prefixes include forming verbs, transforming nouns into verbs, serving as markers indicating something, such as "melihat" functioning as a conjunction "yang", indicating something that has happened in the past in Indonesian, expressing a request, and indicating a number. The meanings associated with each prefix include indicating a place descriptor, the ability to perform desired actions, performing actions based on their basic forms, and performing a specific action.